Perineural Injection of Mecobalamin Versus Dextrose 5% Against Clinical Changes and Electrophysiological Features of Carpal Tunnel Syndrome Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Henry Sugiharto; Masita; Andini, Diah; Try Merdeka Puri (HM Publisher, 2024)
Background: Carpal tunnel syndrome (CTS) is a common compression neuropathy with symptoms of pain, tingling, and numbness in the hands. Perineural injections of steroids and mecobalamin have been shown to be effective in relieving CTS symptoms. This study aims to compare the effectiveness of the perineural injection of mecobalamin and 5% dextrose on clinical changes and electrophysiological features in CTS sufferers. Methods: This research is a pilot study open-label randomized controlled trial conducted at Dr. Mohammad Hoesin General Hospital Palembang. A total of 24 CTS patients were randomly divided into two groups: the mecobalamin group (n=12) and the 5% dextrose group (n=12). Patients in both groups received a single perineural injection. Results: In the mecobalamin group, there were significant improvements in pain scores (NPRS), Boston carpal tunnel questionnaire (BCTQ) - symptom severity scale (SSS), and functional status scale (FSS) after 2 weeks. In the 5% dextrose group, there were also significant improvements in pain scores and BCTQ-SSS and BCTQ-FSS scores. However, the electrophysiological picture did not change significantly after 2 weeks of perineural injection. Comparison between groups showed significant differences in NPRS, BCTQ-FSS, and sensory amplitude. Conclusion: Perineural injection of mecobalamin and 5% dextrose is effective in improving clinical symptoms of CTS. Mecobalamin showed better effects on improving NPRS, BCTQ-SSS, and sensory conduction amplitude than 5% dextrose.